DOP76 Prevalence and healthcare costs of perianal fistulas in Crohn's disease in a nationwide cohort. (25th January 2019) - Nordholm-Carstensen, A; Qvist, N; Højgaard, B; Halling, C; Carstensen, M; Ipland, N-P; Burisch, J
Abstract: Background: Data on the prevalence of perianal fistulas in Crohn's disease (pCF) and the associated healthcare costs remain sparse. This study aimed to determine the prevalence of pCF in a nationwide cohort. Secondary outcomes included the use of biologicals, number of surgical interventions, and direct healthcare costs related to pCF. Methods: All patients registered in the Danish National Patient Registry as having Crohn's disease (CD) between 2010 and 2016 were identified of whom the subpopulation with a pCF diagnosis (complex and simple) or a pCF-related surgical procedure were included. Data on in- and out-patient services were retrieved from the National Patient Registry, which includes data on all patient contacts, including diagnoses as well as diagnostic and treatment procedures. The database uses international classification systems, for instance, the ICD-10. Data were linked with the Danish Case Mix System (Diagnose-Related Groups) to assign costs to outpatient and inpatient services in pCF cases. Results: In total, 17789 patients were identified as having CD in the study period. The prevalence of pCF ranged from 612 (5.1 fistula patients per 100 patients with CD) to 544 (3.1 fistula patients per 100 patients with CD) during the study period. Furthermore, the number of incident perianal fistula cases decreased from 303 cases in 2010 to 144 cases in 2016. In total, 1773 (10%) patients were identified with an incident pCF in the study period of whom 49% were female. Mean age was 33.4 years and mean duration of CD prior to pCF was 366 days. Biological treatment was administered to 46.9% of the patients; of whom, 25.9% were in biological treatment prior to the diagnosis of pCF. In total, 35% were subjected to surgical intervention. The mean number of pCF-related surgical procedures per year was 1.4 per patient. During the study period 17 (0.096%) patients had a stoma performed, whereas 8 (0.045%) had reversal of their stoma. Mean cost from 2010 to 2015 was €21708 per patient (IQR: €2501–28930). In 2016, the total hospital-associated costs for diagnosis and treatment of pCF was €2.3 million, with biologicals being the major expenditure (€911200) followed by surgical interventions (€723600). Healthcare costs for treatment of pCF decreased during the study period mainly due to lowered prices on biologicals. Conclusions: In a Danish nationwide cohort of patients with CD, the prevalence of perianal fistulas decreased in the period from 2010 to 2016. The reason for this needs further elucidation. Only half of the incident cases received biologicals, yet biological treatment was the main expenditure for the entire study population. Healthcare costs for pCF decreased during the study period, but are still high compared with non-pCF IBD patients.